2021
DOI: 10.1093/cercor/bhab093
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity Intermittent Training Enhances Spatial Memory and Hippocampal Neurogenesis Associated with BDNF Signaling in Rats

Abstract: High-intensity intermittent (or interval) training (HIIT) has started to gain popularity as a time-effective approach to providing beneficial effects to the brain and to peripheral organs. However, it still remains uncertain whether HIIT enhances hippocampal functions in terms of neurogenesis and spatial memory due to unconsidered HIIT protocol for rodents. Here, we established the HIIT regimen for rats with reference to human study. Adult male Wistar rats were assigned randomly to Control, moderate-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…For example, 6-week high-intensity interval training (HIIT) increased hippocampal lactate concentration and enhanced mitochondrial biogenesis ( Hu et al, 2021 ). In addition, HIIT also increased hippocampal brain-derived neurotrophic factor (BDNF) expression and protein, which is a necessary regulator for enhancing mitochondrial quality control, and maintaining neuronal function and survival ( Freitas et al, 2018 ; Hu et al, 2021 ; Okamoto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 6-week high-intensity interval training (HIIT) increased hippocampal lactate concentration and enhanced mitochondrial biogenesis ( Hu et al, 2021 ). In addition, HIIT also increased hippocampal brain-derived neurotrophic factor (BDNF) expression and protein, which is a necessary regulator for enhancing mitochondrial quality control, and maintaining neuronal function and survival ( Freitas et al, 2018 ; Hu et al, 2021 ; Okamoto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF belongs to the neurotrophin family of growth factors (Xue et al, 2021) and is expressed at high levels in the developing brain; this protein has been proven to promote neurogenesis. Recently, a number of studies have reported that BDNF plays a crucial role in neurogenesis (Jaworska et al, 2019;Okamoto et al, 2021). The binding of BDNF to TrkB, a neurotrophin receptor, activates various intracellular signaling pathways, including the ERK, CREB and phosphoinositide 3-kinase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing brain, neurogenesis persists in two neurogenic niches (Poiana et al, 2020;Cebrian-Silla et al, 2021;Du et al, 2021). In the sub-granular zone (SGZ) of the dentate gyrus, neurogenesis has been linked to both memory and learning (Okamoto et al, 2021). In the subventricular zone (SVZ), newly formed neurons can migrate to the OB and integrate into neural circuits; this process is important for olfactory recognition memory (Sha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is considerable interest in identifying pharmacological interventions to prevent dementia and AD, life style changes in the form of increased physical activity may offer significant benefit. Exercise greatly enhance neurogenesis, learning and memory in animal models (van Praag et al, 1999a , b ), effects associated with increased expression of brain derived neurotrophic factor (BDNF) in the hippocampus (Adlard et al, 2004 ; Okamoto et al, 2021 ) and decreased amyloid protein levels in transgenic AD mice (Adlard et al, 2005 ). Epidemiological studies suggest that physical activity and fitness significantly reduces cognitive decline and AD (Laurin et al, 2001 ; Lytle et al, 2004 ; Podewils et al, 2005 ; Ross et al, 2016 ).…”
Section: Future Directionsmentioning
confidence: 99%